The Unique Presentation of Massive Ascites Complicating Severe Preeclampsia and HELLP syndrome - Wirawan, Jimmy P. (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To describe a rare case of massive ascites complicating severe preeclampsia and HELLP syndrome. Method: Reporting a case experienced and taken care in our hospital. Result: We report a case of Mrs L, 29 years old, gravid 1, admitted at 35th week gestation, with preeclampsia, HELLP syndrome (thrombocyte 49000/ul, LDH 888 U/l), and IUFD. We found ascites pre-operatively. Cesarean section was conducted. As much as 1.5 litre of ascites was evident during CS. We put intra-abdominal drain and ascites was about 4300 ml, 3800 ml and 1200 ml on 1st, 2nd and 3th day. Patient was discharged after five days of care. One week follow up, patient came with good condition and controlled blood pressure and clinically no evident ascites. Conclusion: Preeclampsia is one of the major causes of maternal mortality and morbidity in the world. Manifestation of preeclampsia can range from mild preeclampsia to full blown eclamptic condition. Herein we presented a case of massive ascites complicating severe preeclampsia and HELLP syndrome. [Indones J Obstet Gynecol 2011; 35-2: 67-9] Keywords: massive ascites, preeclampsia, HELLP syndrome